Genetic determinant of rapid-onset B-cell lymphoma by avian leukosis virus. - Smith, M R (1997)
Infection of 10 day-old chicken embryos with the recombinant avian leukosis virus (ALV) EU-8 induces a high incidence of rapid-onset B-cell lymphoma by insertional activation of the c-myb gene. LR-9, a related ALV with differences from EU-8 in the gag and pol genes, induces rapid-onset lymphoma at only a low incidence. To localize the viral determinant(s) responsible for this biologic difference, we constructed and tested a series of reciprocal chimeras between EU-8 and LR-9 ALVs. The ability to induce rapid-onset lymphoma efficiently was localized to a 925-nucleotide (nt) region of the EU-8 gag gene. Sequence analysis of the region revealed a 42-nt deletion in EU-8 relative to LR-9, as well as some single-nucleotide changes. A mutant virus, delta LR-9, constructed by deleting these 42 nt from LR-9, also induced rapid-onset lymphoma at a high frequency, confirming the biologic significance of this deletion. This deletion removed nt 735 to 776, which lies within a cis-acting RNA element that negatively regulates splicing (NRS). The deletion was shown to cause an increase in splicing efficiency, which may lead to increased production of a truncated myb gene product from an ALV-myb readthrough RNA.